Nursing of a patient with chronic obstructive pulmonary disease complicated with acute respiratory failure and plaque psoriasis (1例慢性阻塞性肺疾病合并急性呼吸衰竭伴斑块状银屑病患者的护理体会) - SHI Mingjie (石明杰); WANG Liangmin (王梁敏); TANG Ling (唐玲); MA Jianling (马建岭); ZHANG Yanxia (张艳霞); LIU Jing (刘静); PAN Mengxue (潘梦雪); ZHAO Dandan (赵丹丹) (中西医结合护理)
This paper summarized the nursing management of a patient with chronic obstructive pulmonary disease (COPD)complicated with acute respiratory failure and plaque psoriasis. Comprehensive nursing interventions such as airway clearance techniques, facial skin care, psoriasis skin care, psychological care and discharge preparation services were carried out to relieve the symptoms, prevent the complications and improve the quality of life of the patient (本文总结1例慢性阻塞性肺疾病(COPD)合并急性呼吸衰竭伴斑块状银屑病患者的护理经验。通过综合护理干预, 如气道廓清技术、面部皮肤护理、银屑病皮肤护理、心理护理及出院准备服务等措施, 预防并发症, 改善患者症状, 有效提高患者生活质量。)